Role of long non-coding RNAs in the regulation of ferroptosis in tumors - Ju, Ying; Lv, Yuanhao; Liu, Xu; Lu, Jing; Shi, Yashen; Guo, Huimin; Xu, Siguang; Tian, Jiaqi; Yang, Jun; Zhong, Jiateng (Frontiers in Immunology, 2025)
Normal cells begin to grow indefinitely and immortalize to form tumor cells after an external stimulus resulting in a genetic mutation. Effective killing of tumor cells is the basis of various cancer therapies. Ferroptosis is a class of cell death types dependent on iron and cellular lipid peroxidation. Tumors themselves are iron-dependent, and conventional radiotherapy also sensitizes cancer cells to ferroptosis. Increasing the sensitivity of tumor cells to ferroptosis may be a potential therapeutic strategy to overcome the resistance mechanisms of conventional cancer therapy. Long noncoding RNAs (LncRNAs) are a class of transcripts more than 200 nucleotides in length that regulate gene expression at multiple levels and are involved in biological processes such as cell differentiation, cell cycle arrest, and maintenance of tumor stemness. Recent studies have found that lncRNAs regulate ferroptosis of tumor cells through multiple mechanisms and may influence or ameliorate tumor resistance to chemotherapeutic agents. With the continuous maturation of nanomaterials technology, it may provide new means for cancer treatment by regulating the levels of ferroptosis-related lncRNAs inside tumors as well as increasing the levels of Fe2+ and ROS inside tumors. In this paper, we systematically introduce the regulatory mechanism of lncRNAs in ferroptosis, the role of ferroptosis in tumor immunotherapy and the application of lncRNAs combined with ferroptosis in nanomaterials, which provides new perspectives for tumor therapy.